The Influence of Organizational Culture, Competence, and Leadership on Work Ethic in the General Affairs Division of the PSDMPK-PMP Secretariat - Pena, Ade Faisal (Priviet Social Sciences Journal, 2021)
This study aims to analyze the influence of organizational culture, competence, and leadership on employee work ethic in the General Affairs Division of the PSDMPK-PMP Secretariat, Ministry of Education and Culture. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to all 60 employees, applying a saturated sampling technique. The data were analyzed using descriptive statistics, correlation analysis, and regression analysis. The findings indicate that organizational culture, competence, and leadership each have a positive and significant effect on work ethic. Organizational culture shows a strong correlation with work ethic (r = 0.629), competence demonstrates a moderate relationship (r = 0.368), and leadership exhibits the strongest correlation (r = 0.716). Simultaneously, the three independent variables significantly influence work ethic, with a coefficient of determination (R²) of 0.745, indicating that 74.5% of the variance in work ethic can be explained by organizational culture, competence, and leadership. Furthermore, the results reveal that organizational support is the most influential indicator within organizational culture, cognitive and non-academic abilities dominate competence, and discipline along with participative decision-making are key aspects of leadership. These findings highlight the importance of strengthening organizational culture, enhancing employee competence, and maintaining effective leadership practices to improve work ethic.This study contributes to the field of human resource management by providing empirical evidence on the relationship between organizational factors and work ethic in the public sector.